Opinion Formation on Environmental Protection: Understanding the Origins of Attitudes Toward Resource Enhancement and Protection in Iowa - Lulu Rodriguez; Olan Farnall; Joel Geske; Jane W. Peterson (Journal of Applied Communications, 1998)
To explain the origins of attitudes toward environmental issues, three alternative explanations for increased concerns toward resource enhancement and protection in Iowa are examined. First, do values explain the popularity of environmental issues? Second, do people experience pollution problems in their local environment and then translate this direct experience into a positive attitude toward the overall importance of the protection of nature? And third, do citizens feel threatened by the increasing extent of the destruction of the state’s environment? This study assesses the relative ability of these three models to explain the importance that citizens attach to environmental protection. It also attempts to provide insights into how a communication campaign can be designed. This on-going campaign, launched in 1995, was aimed to solicit citizen support for efforts to enhance and protect Iowa’s natural resources. Surveying a randomly selected, statewide cross-section who answered a mailed questionnaire, researchers found that each of the three models contributed directly to the opinion-formation process, although the self-interest dimension displayed the strongest direct effect. This finding implies that campaign messages must be framed in a way that stresses the benefits of environmental protection on the individual. Following survey results, print and broadcast messages were designed to answer the oft-repeated question: “What’s in it for me?”